Association between red blood cell distribution width and left ventricular hypertrophy in pediatric essential hypertension - Sun, Xiaodong; Liu, Yang; Liu, Yanyan; Wang, Hui; Liu, Bo; Shi, Lin (Frontiers in Pediatrics, 2023)
Aim: Left ventricular hypertrophy (LVH) is one of the most common types of target organ damage in hypertension. The red blood cell distribution width (RDW) is closely related to many cardiovascular diseases, including hypertension. The aim of this study was to analyze the relationship between the RDW level and LVH in pediatric essential hypertension. Materials and Methods: A total of 429 untreated children and adolescents with essential hypertension were recruited and divided into an LVH group (n = 114) and non-LVH group (n = 315) according to left ventricular mass index (LVMI) and relative wall thickness (RWT) by color Doppler ultrasound. Spearman correlation analysis was used to determine the relationship between RDW and LVMI, RWT. The effect of RDW on LVH was determined using a multivariate logistic regression analysis. To assess the predictive value of RDW on LVH, the receiver operating characteristic (ROC) curve was used. Results: The level of RDW in children with hypertension in the LVH group was significantly higher than that in the non-LVH group (13.0 [12.0, 13.0] vs. 12.4 [12.0, 13.0] %, P = 0.001). The incidence of low and high quantiles of LVH was 21.0% and 32.0%, respectively. Spearman correlation analysis showed that RDW was positively correlated with C-reactive protein (CRP), LVMI, RWT, and red blood cell (RBC) count (P all < 0.05), and negatively correlated with hemoglobin (HGB) level, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) (P all < 0.05). After adjusting for various confounding factors, a multivariate logistic regression model revealed that RDW was an independent risk factor for LVH (OR = 1.946, 95% CI: 1.324–2.861, P = 0.001). The area under the ROC curve of RDW predicting centripetal hypertrophy was 0.700 (95% CI: 0.541–0.859, P < 0.05) in pediatric essential hypertension. Conclusions: Increased RDW levels are an independent risk factor for LVH in pediatric essential hypertension, and RDW may be a predictor of LVH in untreated pediatric essential hypertension.